Influence of drought stress on photosynthetic characteristics and protective enzymes of potato at seedling stage - Jianhui Li; Zhenming Cang; Feng Jiao; Xuejing Bai; Ding Zhang; Ruichang Zhai (Journal of the Saudi Society of Agricultural Sciences)
The influences of drought stress on the photosynthesis rate, the chlorophyll fluorescence parameters, the activity of protective enzymes of potato, and the biomass fresh weights of potato leaves at seedling stage were investigated, using two different varieties of potato with significant difference in drought resistance to carry out potted plant experiment with water control. Under mild and medium drought stresses, the two potato varieties stabilized the photosynthetic organ functions by light capture reduction, heat dissipation and the regulation of enzyme activity. The damage of photosystem II and antioxidant enzyme system was the non-stomatal limitation factors for the decrease of the photosynthesis rate under serious drought stress. The influence on the physiological parameters of potato Kexin No. 1 was weaker than that of potato Kexin No. 12 under drought stresses. The higher photosynthesis rate and stronger activity of protective enzymes were the important physiological reasons for the drought resistance of Kexin No. 1.